Prevalence and causes of blindness and vision impairment among people 50 years and older in Nepal: A national Rapid Assessment of Avoidable Blindness survey - Sailesh Kumar Mishra; Ranjan Shah; Parikshit Gogate; Yuddha Dhoj Sapkota; Reeta Gurung; Mohan Krishna Shrestha; Islay Mactaggart; Ian McCormick; Brish Bahadur Shahi; Rajiv Khandekar; Matthew Burton (PLoS ONE, 2025)
Purpose To determine the prevalence and causes of blindness and vision impairment among people 50 years and older in Nepal. Methods We conducted seven provincial-level Rapid Assessment of Avoidable Blindness (RAAB) cross-sectional, population-based surveys between 2018–2021. Provincial prevalence estimates were weighted to give nationally representative estimates. Sampling, enumeration, and examination of the population 50 years and older were done at the province level following standard RAAB protocol. Results Across seven surveys, we enrolled 33,228 individuals, of whom 32,565 were examined (response rate 98%). Females (n = 17,935) made up 55% of the sample. The age-sex-province weighted national prevalence of blindness (better eye presenting visual acuity <3/60) was 1.1% (95% confidence interval [CI] 1.0–1.2%), and any vision impairment <6/12 was 20.7% (95% CI 19.9–21.5%). The prevalence of blindness was higher in women than men (1.3% [95% CI 1.1–1.5%] vs 0.9% [95% CI 0.7–1.0%]). Age-sex weighted blindness prevalence was highest in Lumbini Province (1.8% [95% CI 1.3–2.2%]) and lowest in Bagmati Province (0.7% [95% CI 0.4–0.9%]) and Sudurpaschim Province (0.7% [95% CI 0.4–0.9%]). Cataract (65.2%) was the leading cause of blindness in our sample, followed by corneal opacity (6.4%), glaucoma (5.8%) and age-related macular degeneration (5.3%). Other posterior segment diseases accounted for 8.4% of cases. Cataract was also the leading cause of severe vision impairment (83.9%) and moderate vision impairment (66.8%), while refractive error was the leading cause of mild vision impairment (66.5%). Conclusion The prevalence of blindness was higher among women than men and varied by province. The Lumbini and Madesh Provinces in the Terai (plains) region had higher prevalence of blindness than elsewhere. Cataract was the leading cause of blindness, severe vision impairment and moderate vision impairment while refractive error was the leading cause of mild vision impairment.